Changing Direction. Perception of the Spanish Cinema in 2014 - Deltell Escolar, Luis; Clemente Mediavilla, Jorge; García Fernández, Emilio C. (Pensar la Publicidad. Revista Internacional de Investigaciones Publicitarias, 2016)
This paper presents the conclusions of a study carried out during the audiovisual season of 2014 that was aimed at seeing the public’s perception of Spanish cinema. To obtain the quantitative data for the experiment, a field survey has been carried out, the mayor on this issue since 2009, with a total sampling of n=1244 people surveyed all over the country. Besides, this quantitative study has been backed up with further data from production, ticket sales and in-depth interviews to members of the film industry. Finally, a qualitative analysis has been carried out to delve into two further aspects: the audience’s tastes and the strategies used by film producers, film directors and other sectors within the film industry. The central aim of this study was to assess what was the perception of the Spanish public on their cinema. Our study reveals that regarding the films produced in Spain a change of trend has occurred. A majority of the people surveyed seem to feel closer and keen on the films of the last season, this being a conclusion reaffirmed with other control data, such as box office sales and impact on the audience.
Keywords: Spanish Cinema; Viewer; Communication; Audiences; Marketing; Film Production.